Ιστορίες Επτανήσιων στον χώρο και τον χρόνο της Ελληνικής Επανάστασης - Γκέκας, Σάκης (Peri Istorias, 2022)
The article shifts the discussion about the Ionian Islands and the Greek Revolution of 1821 from the “Ionian contribution”, as an older historiography put it, to questions about how Ionians interacted with the events and were influenced by the course of the Revolution, as well as the dilemmas that some Ionians faced. Starting from the Ionian Islands as space of preparation for the Revolution, to the armed participation of some Ionians, to the consequences that the Revolution had on the daily lives of many Ionians, the article reveals some of the dimensions of the entangled relationship between Ionians and the Revolution. The position of each island and its proximity to the space of the Greek Revolution, the place of Ionians in the class hierarchy of their societies and the changing British policy towards the Revolution that affected the Ionian State and its citizens are some aspects of this relationship between Ionians and the Greek Revolution.